Perancangan dan Implementasi Sistem Informasi Inventaris Barang Berbasis Web pada Sekolah Tinggi Theologi Ikat - Aqhilla Davina Prilla Puan Maharani; Ageng Maruti Ningsih; Maulana Ardhiansyah (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2026)
Inadequately managed asset inventories remain a common issue in educational institutions. Sekolah Tinggi Teologi IKAT (STT IKAT) in South Jakarta still performs inventory recording manually using Microsoft Excel, resulting in several problems, including data inconsistencies, difficulties in monitoring assets, the absence of location and transfer history records, and delays in generating inventory reports. This study aims to develop a Web-Based Inventory Information System as a digital approach to asset management at STT IKAT. The system was developed using an iterative method consisting of requirements identification, design, implementation, testing, and evaluation stages. System design employed UML modeling, including Use Case Diagrams, Activity Diagrams, and Sequence Diagrams, supported by an Entity Relationship Diagram (ERD) for database design. The developed system provides two user access levels, namely Super Admin and Admin, and includes features for managing inventory data, recording asset locations and conditions, tracking inter room transfers, handling borrowing activities, and generating room-based inventory reports. The implementation results indicate that the system contributes to more effective inventory management, enables real-time asset monitoring, and produces reports more quickly and accurately than the previous manual approach.